2016
DOI: 10.1095/biolreprod.115.136721
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PIWIL1 Isoforms and Their Expression in Bovine Testes, Oocytes, and Early Embryos1

Abstract: PIWI proteins are members of the larger Argonaute family and bind to specific 24-32 nucleotide RNAs called PIWI-interacting RNAs (piRNAs). PIWI-interacting RNAs direct PIWI-mediated suppression of retrotransposon expression in the male germline in humans and mice, but their roles in bovine reproduction and embryogenesis are unknown. Although the majority of research in mammals has focused on the functions of PIWI proteins during spermatogenesis, this family of proteins and their associated piRNAs have recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
1
21
0
Order By: Relevance
“…Following discoveries in Drosophila , one mouse PIWI homolog, MIWI (PIWI‐like 1, or PIWIL1), was shown to be a cytoplasmic protein required for normal mammalian spermatogenesis (Deng et al., ). The expression of PIWIL1 begins at 14 days post‐partum (dpp) in pachytene spermatocytes and persists to the round spermatid stage (Deng et al., ) with similar patterns in the dog (Stalker et al., ) and bull (Russell et al., ). PIWIL1 functions to maintain GSCs through post‐transcriptional gene silencing (PTGS) of transposable elements (TEs).…”
Section: Piwi and Piwi‐like Proteinsmentioning
confidence: 94%
See 3 more Smart Citations
“…Following discoveries in Drosophila , one mouse PIWI homolog, MIWI (PIWI‐like 1, or PIWIL1), was shown to be a cytoplasmic protein required for normal mammalian spermatogenesis (Deng et al., ). The expression of PIWIL1 begins at 14 days post‐partum (dpp) in pachytene spermatocytes and persists to the round spermatid stage (Deng et al., ) with similar patterns in the dog (Stalker et al., ) and bull (Russell et al., ). PIWIL1 functions to maintain GSCs through post‐transcriptional gene silencing (PTGS) of transposable elements (TEs).…”
Section: Piwi and Piwi‐like Proteinsmentioning
confidence: 94%
“…One of the most important and widely recognized pathways controlling TE expression during reprogramming is the PIWI (P‐element‐Induced WImpy testes) pathway, named for the phenotype of Drosophila mutants carrying genetic defects in this pathway. Much of the initial mechanistic work has been performed in Drosophila and murine models; however, recent studies (Kowalczykiewicz, Pawlak, Lechniak, & Wrzesinski, ; Russell et al., , ; Stalker, Russell, Co, Foster, & LaMarre, ) have confirmed that these pathways are also present in domestic animals and appear to play similar roles. Table summarizes the PIWI proteins in different species.…”
Section: The Piwi Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, piRNAs are associated with the PIWI proteins and other adjuncts, to form the piRNA induced silencing complex (piRISC) in germ granules (Figure 3 ). Taking into account the expression patterns of piRNAs and PIWI proteins in male germ cells and early embryos, we believe that piRISC participates in the gene regulation at the transcriptional, post-transcriptional and even translational levels to some extent [ 34 , 35 ]. The piRISC regulates gene silencing and maintains the genome stability through cleaving of the target mRNAs, or directing the DNA methylation dependent silencing towards target loci in the genome [ 36 ].…”
Section: Introductionmentioning
confidence: 99%